Resonancia (2017)
"This project started as a personal reflection on my true essence and my place in the world. The result was an introspective space given by the interpretation of mythology and the process of personal awareness. Based on this idea the next question was introduced: based on the mythological narratives, can introspective spaces which bring us closer to the transcendental arise? In order to solve this, Nietzsche's concept of the myth as a symbol was used next to the Mirror stage of Jacques Lacan." -- Tomado del Formato de Documento de Grado.